Development of a Companion Diagnostic PD-L1 Immunohistochemistry Assay for Pembrolizumab Therapy in Non–Small-cell Lung Cancer. Issue 6 (July 2016) - Roach, Charlotte; Zhang, Nancy; Corigliano, Ellie; Jansson, Malinka; Toland, Grant; Ponto, Gary; Dolled-Filhart, Marisa; Emancipator, Kenneth; Stanforth, Dave; Kulangara, Karina
Abstract : A companion diagnostic assay was codeveloped by Dako for pembrolizumab non–small-cell lung cancer clinical trials to detect PD-L1 expression by immunohistochemistry (IHC). This automated IHC assay has been analytically verified and validated using Dako's autostainer Link 48 and 22C3 mouse anti-PD-L1 monoclonal antibody to detect the PD-L1 expression in formalin-fixed paraffin-embedded human tumor tissue specimens. The PD-L1 22C3 IHC assay was optimized for high sensitivity and specificity. Repeatability and reproducibility studies were conducted at Dako and at 3 Clinical Laboratory Improvement Amendments certified laboratories during assay development. The studies included: intersite and intrasite, interobserver and intraobserver, interinstrument, interoperator, interday, and interlot, and intraday and intrarun. All precision studies performed at Dako and external laboratories achieved >85% point-estimate agreements for all 3 agreement types (negative, positive, and overall). A clinical cutoff (tumor proportion score ≥50%) of PD-L1 expression was determined and evaluated through a phase 1 clinical trial (KEYNOTE-001) for advanced non–small-cell lung cancer patients treated with pembrolizumab. The treatment effect of pembrolizumab in the 61 subjects who had a tumor PD-L1 of tumor proportion score ≥50% was substantial, with an overall response rate of 41% (95% confidence interval, 28.6-54.3) as compared with 20.6% (95% confidence interval, 15.5-26.5) observed in the 223 subjects irrespective of PD-L1 status. PD-L1 IHC 22C3 pharmDx is a sensitive, precise, and robust companion diagnostic assay, which will facilitate safe and effective use for pembrolizumab in cancer patients.